2003
DOI: 10.1016/s1607-551x(09)70505-4
|View full text |Cite
|
Sign up to set email alerts
|

Eyelid Tumors in Southern Taiwan: A 5‐Year Survey from a Medical University

Abstract: This retrospective case analysis investigated the epidemiology of eyelid tumors in a subtropical area. The study assessed the proportion of all eyelid tumors that were malignancies, the accuracy of diagnosis, and surgical results. We retrospectively collected all cases of eyelid tumors in the Department of Ophthalmology, Kaohsiung Medical University, Taiwan, between January 1994 and December 1998. Among the 144 cases collected, about half of the tumors were located in the upper eyelids and the other half in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
2
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 24 publications
6
19
2
9
Order By: Relevance
“…(Hilovsky, 1995;Chang et al, 2003;Takamura and Yamashita, 2005;Lin et al, 2006;Coroi et al, 2010) Male dominance was seen in basal cell carcinoma in accordance with previous findings (Frost et al, 1998). Basal cell carcinoma is most common in the lower eyelid, and medial canthal area in the ocular adnexal region (Margo and Waltz, 1993;Allali et al, 2005;Mannor et al, 2009).…”
Section: Discussionsupporting
confidence: 76%
“…(Hilovsky, 1995;Chang et al, 2003;Takamura and Yamashita, 2005;Lin et al, 2006;Coroi et al, 2010) Male dominance was seen in basal cell carcinoma in accordance with previous findings (Frost et al, 1998). Basal cell carcinoma is most common in the lower eyelid, and medial canthal area in the ocular adnexal region (Margo and Waltz, 1993;Allali et al, 2005;Mannor et al, 2009).…”
Section: Discussionsupporting
confidence: 76%
“…Different studies have reported various frequencies of benign tumors some of which are similar to our series. For example, 3 separate studies from China, Southern Taiwan and South Korea the most frequent benign tumors were, in descending order, nevus, papilloma, and cyst 345. The most prevalent benign masses in the studies by Kersten et al 6.…”
Section: Discussionmentioning
confidence: 98%
“…Japonya, Tayvan ve Güney Kore'de yapılan çeşitli çalışmalarda nevüslerin papillom ve kistlere oranla daha sık görüldüğü belirtilmiştir. 6,8,17 İyi huylu gözkapağı tümörleri 50 yaş üzerinde daha sıktır. 3,5 Çalışmamızın sonucunda olguların yaş ortalamasının 53 yıl ve %65'inin 50 yaş üzerinde olduğu belirlenmiştir.…”
Section: Discussionunclassified
“…1,[5][6][7] Perioküler deri lezyonlarının çoğu iyi huylu olmasına rağmen malign tümörlerin hayatı tehdit edici potansiyelleri nedeniyle ayırıcı tanının yapılması büyük önem taşımaktadır. 5,8,11 Gözkapağı tümörlerine yaklaşımın belirlenmesinde iyi bir anamnez ve lezyonun klinik özellikleri dikkate alınmalıdır. [11][12][13] Gözkapağında görülen iyi huylu tümörlerin yavaş büyümesi ve sıklıkla asemptomatik olması nedeniyle birçok hasta hekime başvurmamakta, tanı konan olgularda eksizyon nadiren uygulanmakta ve histopatolojik inceleme birçok olguda yapılmamaktadır.…”
Section: Gi Riflunclassified